Metabolic remodeling in cardiac hypertrophy and heart failure with reduced ejection fraction occurs independent of transcription factor EB in mice - Dörmann, Niklas; Hammer, Elke; Struckmann, Karlotta; Rüdebusch, Julia; Bartels, Kirsten; Wenzel, Kristin; Schulz, Julia; Gross, Stefan; Schwanz, Stefan; Martin, Elisa; Fielitz, Britta; Pablo Tortola, Cristina; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: A metabolic shift from fatty acid (FAO) to glucose oxidation (GO) occurs during cardiac hypertrophy (LVH) and heart failure with reduced ejection fraction (HFrEF), which is mediated by PGC-1α and PPARα. While the transcription factor EB (TFEB) regulates the expression of both PPARGC1A/PGC-1α and PPARA/PPARα, its contribution to metabolic remodeling is uncertain.Methods: Luciferase assays were performed to verify that TFEB regulates PPARGC1A expression. Cardiomyocyte-specific Tfeb knockout (cKO) and wildtype (WT) male mice were subjected to 27G transverse aortic constriction or sham surgery for 21 and 56 days, respectively, to induce LVH and HFrEF. Echocardiographic, morphological, and histological analyses were performed. Changes in markers of cardiac stress and remodeling, metabolic shift and oxidative phosphorylation were investigated by Western blot analyses, mass spectrometry, qRT-PCR, and citrate synthase and complex II activity measurements.Results: Luciferase assays revealed that TFEB increases PPARGC1A/PGC-1α expression, which was inhibited by class IIa histone deacetylases and derepressed by protein kinase D. At baseline, cKO mice exhibited a reduced cardiac function, elevated stress markers and a decrease in FAO and GO gene expression compared to WT mice. LVH resulted in increased cardiac remodeling and a decreased expression of FAO and GO genes, but a comparable decline in cardiac function in cKO compared to WT mice. In HFrEF, cKO mice showed an improved cardiac function, lower heart weights, smaller myocytes and a reduction in cardiac remodeling compared to WT mice. Proteomic analysis revealed a comparable decrease in FAO-and increase in GO-related proteins in both genotypes. A significant reduction in mitochondrial quality control genes and a decreased citrate synthase and complex II activities was observed in hearts of WT but not cKO HFrEF mice.Conclusions: TFEB affects the baseline expression of metabolic and mitochondrial quality control genes in the heart, but has only minor effects on the metabolic shift in LVH and HFrEF in mice. Deletion of TFEB plays a protective role in HFrEF but does not affect the course of LVH. Further studies are needed to elucidate if TFEB affects the metabolic flux in stressed cardiomyocytes.